Book review: Hevina S. Dashwood’s The rise of global corporate social responsibility: Mining and the spread of global norms - LIM, Alwyn (Institutional Knowledge at Singapore Management University, 2014)
Given the dramatic rise in the globalization of production of goods and services since the 1990s, it is somewhat surprising that scholarly attention to the consequences of those globalization processes has been slow to recognize the cross-national dimensions of corporate social responsibility, much less coalesce around definitive research pro grams. Hevina Dashwood's examination of the impact of global norms on the mining industry is a study that brings several theo retical and empirical threads together in a coherent manner that can inform the work of globalization, organizations, and manage ment scholars interested in issues in corpo rate social responsibility. Corporate social responsibility (CSR) - business attention to social and environmental issues beyond legal compliance - has long been at the center of controversies for companies in the extractive industries, of which mining companies have been heavily scrutinized by nongovernmen tal organizations and government regulatory agencies. In The Rise of Global Corporate Social Responsibility, Dashwood asks why mining companies have been receptive to CSR efforts to constrain their activities despite the increased scrutiny and constraint on their activities that CSR engagement would bring. Dashwood's answer, based on her analysis of CSR in the global mining indus try and case studies of how three Canadian mining companies responded to external CSR pressures, offers contributions to the lit erature on CSR that are much needed: a focus on CSR at the global level, a three-level insti tutional framework, and an analysis of inter nal organizational dynamics that contributes to CSR engagemen